2008
DOI: 10.1002/jmri.21575
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of diffusion‐weighted imaging in differentiating benign from malignant ovarian lesions

Abstract: Purpose: To clarify the diagnostic accuracy of diffusionweighted imaging (DWI) in differentiating benign from malignant ovarian lesions. Materials and Methods:We retrospectively analyzed magnetic resonance images of 123 ovarian lesions in 119 patients. We defined lesions with abnormal signal intensity as malignancy and assessed the location of abnormal intensity within the lesions on DWI. We also assessed the mean and lowest apparent diffusion coefficient (ADC) values of the solid portion for each ovarian lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
4
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 28 publications
13
129
4
7
Order By: Relevance
“…We believe no report has demonstrated the usefulness of DWI and ADC value in diagnosing a malignant Brenner tumor, and their clinical usefulness in discriminating benign from malignant ovarian tumors has been controversial. [10][11][12] Takeuchi's team 10 reported a tendency of the ADC of the solid component of malignant/borderline malignant ovarian tumors to be lower than that of benign ovarian tumors, probably because of the higher cellularity and more enlarged nuclei in the malignant/borderline tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe no report has demonstrated the usefulness of DWI and ADC value in diagnosing a malignant Brenner tumor, and their clinical usefulness in discriminating benign from malignant ovarian tumors has been controversial. [10][11][12] Takeuchi's team 10 reported a tendency of the ADC of the solid component of malignant/borderline malignant ovarian tumors to be lower than that of benign ovarian tumors, probably because of the higher cellularity and more enlarged nuclei in the malignant/borderline tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Thomassin-Naggara 11 and Fujii 12 and their associates demonstrated that ADC measurement did not contribute to the diŠerentiation of benign from malignant ovarian mass because of the frequently low ADC value of benign ovarian tumors, such aŝ broma,ˆbrothecoma, cystadenoˆbroma, teratoma, and endometrial cyst, and the usually high ADC value of malignant ovarian tumors, such as serous or mucinous borderline malignant tumor and metastatic tumor.…”
Section: Discussionmentioning
confidence: 99%
“…that ADC values are not useful for differentiating benign from malignant adnexal masses (Katayama et al, 2002;Fujii et al, 2008). Thomassin-Naggara et al (2009) demonstrated that DWI signal intensity is an accurate tool for predicting benignity of complex adnexal masses, but ADC measurements did not contribute to differentiating benign from malignant adnexal masses.…”
Section: 3407 Differentiation Of Benign From Malignant Adnexal Massementioning
confidence: 99%
“…Some studies showed that ADC value is useful in discriminating benign from malignant masses (Takeuchi et al, 2010;Li et al, 2012;Zhang et al, 2012). But on the contrary, the results of the studies by Thomassin-Naggara et al (2009), Katayama et al (2002), and Fujii et al (2008) demonstrated that ADC measurements did not contribute to differentiating benign from malignant adnexal masses.…”
Section: Introductionmentioning
confidence: 98%
“…8 This is thought to be due to keratin and solid RP, making them unreliable in distinguishing benign from malignant teratomas. 9 The plain film appearance of MT can be a non-calcified mass. With ultrasonography, they frequently appear as a hypoechogenic mass with slight posterior enhancement.…”
Section: Imagingmentioning
confidence: 99%